Contemporary U.S. Latino/ A Literary Criticism
XIV, 284 p.
Keywords: Please note this is a 'Palgrave to Order' title (PTO). Stock of this book requires shipment from an overseas supplier. It will be delivered to you within 12 weeks. This is the first compilation of essays to bring together the most important U.S. Latino/a literary criticism of the last decade. This timely text has been long in coming as U.S. Latino/a literary criticism has grown exponentially throughout U.S universities since 1995.